Employee well-being in the spotlight: a study on the quality of life of workers with celiac disease - Greutter, Zoltán Gergely; Greutter-Gregus, Éva; Szira, Zoltán; Dr. Varga, Erika (Studia Mundi – Economica, 2023)
Human resource management (HRM) is A set of strategies and practices used in organisations to recruit, select, develop and maintain labour force. HRM plays a key role in ensuring the well-being and effectiveness of employees. This paper focuses on the relationship between celiac disease and HRM. The role of HRM in the case of celiac disease lies in the support and integration of employees. HRM activities can help to provide employees with appropriate nutritional options, such as the availability of gluten-free food and information, monitoring employees’ health and well-being, and adapting working conditions and employee needs. Initiatives such as educating and raising awareness of celiac disease among employees, and adapting work environments and organisational policies to specific dietary needs, can contribute to a better workplace experience and performance for employees with celiac disease. Our paper highlights the importance of HRM for employees with celiac disease and emphasises the importance of HRM measures that provide them with the right support and conditions, contributing to employee health, satisfaction and productivity, and thus to the long-term success of the organisation.